Review of Corporate Social Responsibility (CSR) Regulations in Supporting Development in West Java: Kajian Regulasi Corporate Social Responsibility (CSR) Dalam Mendukung Pembangunan di Jawa Barat - Dwiandini, Aprilia; Laksono, Bayu Adi (Progress In Social Development, 2023)
In improving the quality of development in West Java, the local government involves the social responsibility of companies through the regulation of Corporate social responsibility policies/corporate environmental social responsibility/environmental development partnership programs in West Java along with optimization in its implementation. In this study, researchers used descriptive research methods with qualitative approach methods, and data collection techniques using literature studies. The data analysis used is the SWOT analysis method so that it is found things that are strengths in West Java's CSR regulatory policies, weaknesses, opportunities in improving the quality of their implementation and threats that can hinder the implementation of CSR in supporting development in West Java. Dalam meningkatkan kualitas pembangunan di Jawa Barat, Pemerintah Daerah melibatkan kewajiban sosial dari perusahaan-peusahaan melalui regulasi kebijakan mengenai program Corporate Social Responsibility (CSR) di Jawa Barat berikut dengan optimalisasi dalam implementasinya. Dalam kajiannya, peneliti menggunakan pendekatan kualitatif dalam penelitiannya dan menggunakan metode penelitian deskriptif, untuk pengumpulan data menggunakan studi literatur/kajian kepustakaan. Teknik analisis datanya menggunakan metode analisis SWOT sehingga ditemukan hal-hal yang menjadi keunngulan dalam kebijakan regulasi CSR Jawa Barat, kelemahan, peluang dalam peningkatan kualitas pelaksanaannya dan ancaman yang dapat menghambat implementasi CSR tersebut dalam mendukung pembangunan di Jawa Barat